Writing the trail : five women's frontier narratives - Lawrence, Deborah (University of Iowa Press, 2006)
For a long time, the American West was mainly identified with white masculinity, but as more women's narratives of westward expansion came to light, scholars revised purely patriarchal interpretations. Writing the Trail continues in this vein by providing a comparative literary analysis of five frontier narratives--Susan Magoffin's Down the Santa Fe Trail and into Mexico, Sarah Royce's A Frontier Lady, Louise Clappe's The Shirley Letters, Eliza Farnham's California, In-doors and Out, and Lydia Spencer Lane's I Married a Soldier--to explore the ways in which women's responses to the western e.